2019
DOI: 10.1016/j.pcad.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Exercise Training on Left Ventricular Ejection Fraction in Heart Failure with Reduced Ejection Fraction: A 10-year Update

Abstract: In clinically stable HFrEF patients, MICT is an effective therapy to attenuate LV remodeling with the greatest benefits occurring with long-term (≥6 months) training. HIIT performed for 2 to 3 months is superior to control, but not MICT, for improvement of LVEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 47 publications
(105 reference statements)
11
52
0
5
Order By: Relevance
“…It is recommended that all patients with established CHF (regardless of left ventricular ejection fraction) should be enrolled in an exercise-based cardiac rehabilitation programme with a multi-faceted approach 3,48-51 ( Table 5) [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] . This may also apply to patients with cardiac implantable electronic or ventricular assistant devices.…”
Section: Chfmentioning
confidence: 99%
“…It is recommended that all patients with established CHF (regardless of left ventricular ejection fraction) should be enrolled in an exercise-based cardiac rehabilitation programme with a multi-faceted approach 3,48-51 ( Table 5) [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] . This may also apply to patients with cardiac implantable electronic or ventricular assistant devices.…”
Section: Chfmentioning
confidence: 99%
“…The decreased exercise capacity and endothelial dysfunction in patients with chronic heart failure can be improved by regular physical exercise. 25 Further, aerobic exercise training improves both oxygen utilization and ejection fraction in elderly patients with heart failure26,27 and reduces arterial stiffness in older adults. 28 …”
Section: Introductionmentioning
confidence: 99%
“…After acute myocardial infarction, Jiang et al showed that CR significantly improved LVEF [ 17 ], unlike what was concluded by McGregor et al [ 18 ]. Also, in patients with heart failure with reduced ejection fraction, a meta-analysis of exercise training on LVEF showed that moderate-intensity continuous training significantly increased LVEF (95% confidence interval, CI, 2.08 to 5.50%) [ 19 ]. On the contrary, McKelvie et al showed no significant impact [ 20 ].…”
Section: Discussionmentioning
confidence: 99%